Dietary Supplements: A Survey of the Opinion of First-Year Professional Pharmacy Students - Bisrat Hailemeskel; Fekadu Fullas (Diabetes Research, 2022)
Pharmacists need to be at the forefront in advising consumers of dietary supplements (DS) about quality, claims, labeling, safety, efficacy, DS-drug interactions, and other aspects. Yet, the knowledge base of pharmacists and pharmacists-in-training about DS appears to be below expectation. Objective The goal of the study is to evaluate pharmacy student opinions about DS. Methodology A survey questionnaire was developed, tested, and distributed among students who were enrolled in the Drug Information class, which is a 2-credit hour mandatory course for all first professional pharmacy students at Howard University, College of Pharmacy. The data was analyzed using SPSS statistical analysis software. Results A total of 42 students (15 male, 27 female) participated in the survey. Of these, 25 respondents (59.5%) felt comfortable about their knowledge of DS, while only 14 (33.4%) reported participation in counselling (p=0.0281). Most respondents (29; 69%) had used DS in the past, while 21 (50%) claimed they used DS at the time of the survey. To a specific query in the questionnaire regarding lycopene-containing food items, 28 (66.7%) agreed they would use such foods in the future for health benefits. Analysis of the survey data revealed no statistical differences between the responses of male and female students (p>0.05 for all the five questionnaire items). Conclusion In a survey of 42 pharmacy students at Howard University College Pharmacy, over half (59.5%) felt comfortable about their knowledge of DS. About one-third students (33%) reported they were involved in patient counseling and interaction. Over two-third respondents (69%) took DS in the past, while half were taking DS at the time of the survey.